Experimental investigation on the post-fire performance of reactive powder concrete columns - Kadhum, Mohammed; Mahdi, Zainab; Funfakh, Yousif; Mohammed, Zaid; Abdulraheem, Mustafa; Gkantou, Michaela (Scientific Review Engineering and Environmental Sciences (SREES), 2021)
The increased use of reactive powder concrete (RPC) in concrete structures has attracted attention towards the structural behavior of RPC in fires. This work examines experimentally the performance of RPC and NSC columns subjected to 25% of the ultimate load and exposed to direct fire flame for a period of 30 and 60 min at various temperature levels. The paper aims to evaluate the maximum temperature level and fire duration that can be withstood by this type of concrete columns. The results show that the failure mode of RPC columns without reinforcement is a sudden shear failure, whereas the failure mode of reinforced RPC columns is a crushing failure with rupture of certain ties. The RPC columns at high temperatures spall intensively; additionally, the ultimate strength clearly decreases compared to the NSC columns at the same conditions.